Hooglied, liggaam en die mistikus, Sint Teresa van Avila (1515–1582) - Viviers, Hennie (HTS teologiese studies, 2002)
Song of Songs, body and the mystic, St Teresa of Avila (1515 – 1582)In this article the interaction between an allegorical (tropological) understanding of the Song of Songs, the body and the internalized societal values of the sixteenth century Spanish mystic, St Teresa of Avila will be highlighted. Our bodies are central in our symbolizing activities and this confirms that we are (animated) bodies. St Teresa cannot escape her body, not even in the elevated spiritual state of the unio mystica, utilizing the words of love in the Song to voice the soul’s glowing love for Christ. The body’s “voice” is always present, in spite of her societal dualistic values of prioritising the spirit at the expense of the body and it even subtly enhances self-realisation. The repressed body always returns. The “text” of the body onto which is “written” societal values becomes an important source of exposing a society’s hidden ideologies.